Wherefore Doesnt Mean Why Either (Global Journal of Human-Social Science, 2023)
In R omeo and Juliet Juliet says O Romeo Romeo wherefore art thou Ro meo This has been translated as meaning why are you Romeo A different interpretation comes from wherefore itself and should be used instead Fore Fore is at the end of wherefore and it means before as shown by words like forearm and forewarned At a wedding a priest might say do you swear before all your family and friends And it should be noted that given that Shakespeare wrote Romeo and Juliet hundreds of years ago English was closer to German that it is now and that the German word for with what is womit which literally translates into where with There is also a line in Romeo and Juliet that ends with for thou hast need Shakespeare Rome and Julie 1597 Act 4 Scene 3